Factors associated with the usage of mobile technology devices among UiTM English language lecturers / Wan Nazihah Wan Mohamed, Zurina Ismail and Muhammad Saiful Anuar Yusoff - Wan Mohamed, Wan Nazihah; Ismai, Zurina; Yusoff, Muhammad Saiful Anuar (2016)
The development of information and communication technology (ICT) has initiated elearning pedagogies into the language curriculum that exhibits the vision of lifelong learning and knowledge based society. Due to this, the Academy of Language Studies has integrated online assessments as to fulfil the need to integrate e-learning in teaching and learning practices. Being the biggest university in Malaysia, Universiti Teknologi MARA (UiTM) faces the problem of having inadequate classrooms due to budget constraint. Problems in providing sufficient computer and internet facilities could be overcome with the utilization of mobile technology devices into teaching and learning activities. However, this approach requires the educators to equip themselves with relevant skills in using mobile technologies. Based on the literature of technology acceptance, this study aims to identify the factors that affect UiTM English language lecturers' behaviour intention to adopt mobile technology. Questionnaires are distributed through simple random sampling method and analyses of the findings include Statistical Package for Science (SPSS) program and Structural Equation Modelling (SEM). The analysis will consequently identify the factors that can be used to explain user behaviour of the English language lecturers in UiTM. The result may help the educators to acquire relevant skills and assist UiTM to take efficient measures to promote the usage of mobile technologies in its teaching and learning practices. In addition, it also supports the national research agenda in providing better quality of life and innovative human capital.